Penerapan Lembar Kerja Problem Based Learning untuk Melatihkan Keterampilan Pemecahan Masalah Calon Guru IPA - Dhita Ayu Permata Sari; An Nuril Maulida Fauziah; Wahyu Budi Sabtiawan; Ahmad Qosyim (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
This study aims to describe the implementation of problem-based learning to practice problemsolving skills. The research sample is Class A students in the Science Education Department of Science Education Class of 2020-2021 who program Biophysics courses in the Even Semester of 2021-2022. Sampling using purposive sampling technique. The method used in this research is a pre-experimental design with a one shot case study design. The research data were analyzed using quantitative descriptive analysis. The results of the analysis show that problem solving skills have increased after three implementations of learning implementation with a score range of above 85% and is included in the very good category. The conclusion of this research is that problem-based learning guided by appropriate worksheets and regular guidance can improve students' problem-based solving skills. However, improving these skills requires repetition and longer time in learning. Keywords: Problem Based Learning, Problem Solving Skills, Student Worksheet, Pre-service Teacher